2020
DOI: 10.1088/1674-1056/ab9c01
|View full text |Cite
|
Sign up to set email alerts
|

tP40 carbon: A novel superhard carbon allotrope*

Abstract: In this work, a novel carbon allotrope tP40 carbon with space group P4/mmm is proposed. The structural stability, mechanical properties, elastic anisotropy, and electronic properties of tP40 carbon are investigated systematically by using density functional theory (DFT). The calculated elastic constants and phonon dispersion spectra indicate that the tP40 phase is a metastable carbon phase with mechanical stability and dynamic stability. The B/G ratio indicates that tP40 carbon is brittle from 0 GPa to 60 GPa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…First-principles calculations based on density functional theory (DFT) are among the most reliable and popular microscopic theories in material science. This method has a high ability to predict the material structures and properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Yang et al [ 21 ] predicted a novel high-pressure superhard BN phase at high pressure through a developed particle swarm optimization (PSO) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculations based on density functional theory (DFT) are among the most reliable and popular microscopic theories in material science. This method has a high ability to predict the material structures and properties [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Yang et al [ 21 ] predicted a novel high-pressure superhard BN phase at high pressure through a developed particle swarm optimization (PSO) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the similarity-based match is performed for a set of crystalline allotropes from the literature (Figure S7). The pbz/cF288 training allotrope consisting of acetylenes and 6-rings matches the three graphdiyne ( GDY-1 , GDY-2 , and GDY-3 ) crystal structures reported by Matsuoka et al 13 4 6 T10 of the training set and oC14 predicted by Yang et al are determined to be similar, both being tubulanes containing 4-, 6-, and 8-tubes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The pbz/cF288 training allotrope consisting of acetylenes and 6-rings matches the three graphdiyne ( GDY-1 , GDY-2 , and GDY-3 ) crystal structures reported by Matsuoka et al 13 4 6 T10 of the training set and oC14 predicted by Yang et al are determined to be similar, both being tubulanes containing 4-, 6-, and 8-tubes. The tubulane tP40 predicted by Liu et al . is paired with tubulane fer with a comparable tubular geometry of the training set.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[94] A metastable semiconductor tP40 carbon phase (Figure 33; space group P4/mmm; Young's modulus 540 GPa) as indicated by DFT-studies is found to be brittle in the range of 0-60 GPa and ductile in the range of 70-100 GPa. [95] This carbon form can be considered as a superhard material. According to DFT calculations, the new structure o-C 240 , [96] which is a 3D semiconducting and superhard material (Vickers hardness 45 GPa, higher than most ceramics; in other report [97] the hardness is 56.3 GPa) with an orthorhombic unit cell and sp 2 -sp 3 (ratio 1 : 5) hybridization can be formed (Figure 34) during thermal conversion of the 2D polymeric C 60 precursor at high temperature and pressure (30 GPa and 1500 K) subjected to uniaxial compression.…”
Section: Superhard Carbonsmentioning
confidence: 99%